CHARACTER EVOLUTION PSYCHOLOGICAL BASIS (Scientific journal of the Fergana State University, 2024)
The problem of the formation of characters, the interpretation of its diverse world is embodied in the basis of artistic work. In the process of looking into the world of images in the work of art, reactions were expressed to views such as the formation of characters at the character level, their place in the development of events. From these concepts, it can be understood that attention was paid to the artist's skill in creating an artistic image, and some novels were addressed in this regard.